Vortex-Assisted Ionic Liquid Microextraction Coupled to Graphite Furnace Atomic Absorption Spectrometry for Preconcentration and Determination of Trace Levels of Cadmium in Real Samples - Chamsaz, Mahmoud; Sarafraz Yazdi, Ali; Dousti, Fatemeh (Asian Journal of Chemistry, 2013)
A simple and rapid vortex assisted ionic liquid based liquid-liquid microextraction technique was proposed for preconcentration of trace levels of cadmium. According to this method, the extraction solvent was dispersed into the aqueous sample by the assistance of vortex agitator. Cadmium preconcentration was mediated by chelation with ammonium pyrroldinedithiocarbamate and an ionic liquid, 1-hexyl-3-methylimidazolium hexafluorophosphate ([Hmim][PF6]), was chosen as the extraction solvent to extract the hydrophobic complex. Several variables such as sample pH, concentration of ammonium pyrroldinedithiocarbamate, volume of [Hmim][PF6] and extraction time were investigated in details and optimum conditions were obtained. Under the optimum conditions, the limit of detection (LOD) was 0.01 μg L-1 for Cd and relative standard deviation (RSD %) for five replicate determinations of 0.05 μg L-1 was 5.2 %. The results for determination of cadmium in reference material, tap water and apple samples demonstrated the accuracy, recovery and applicability of the presented method.